Technology for diagnosing the effectiveness of an investment portfolio taking into account the strategic risk of emergency: the factor of economic security - ANATOLYEVNA, BURDINA ANNA; TIMOFEEVNA, MANAENKOVA ELENA; VALELEVNA, MOSKVICHYOVA NATALYA (The journal of contemporary issues in business and government, 2021)
Annotation:The technology of forming an investment portfolio, the problems of forming a portfolio in the current conditions are investigated. The approaches to assessing the profitability and risk of the investment portfolio are considered. The concept of strategic emergency risk is introduced (for example, the pandemic of the coronavirus infection COVID-19). The necessity of forecasting such risks, the impact on the economic security of companies, that is, on the profitability and risk of the investment portfolio, is substantiated. A technology has been developed to diagnose the effectiveness of the investment portfolio, taking into account the strategic risk of emergency as a factor of economic security of enterprises. Practical implementation of the developed technique is carried out.